2003
DOI: 10.1007/s00464-002-8771-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroma following endoscopic extraperitoneal inguinal hernioplasty

Abstract: Although seroma is a frequent minor morbidity after TEP, it has no impact on postoperative recovery. Because all seromas invariably resolve, expectant treatment with observation is recommended. Inguinoscrotal hernia carries a four-fold increased risk of developing seroma after TEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
94
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 18 publications
6
94
1
Order By: Relevance
“…This expected finding was absent in our study. The seroma formation (4% in each group) in our study was comparable with the findings of previous studies (1.9-23%) [5,[14][15][16]. However, although wound infection up to 2.8% has been reported by a few studies in the [14], this complication was not experienced by any of our patients nor in several other reported studies [5,6].…”
Section: Discussionsupporting
confidence: 92%
“…This expected finding was absent in our study. The seroma formation (4% in each group) in our study was comparable with the findings of previous studies (1.9-23%) [5,[14][15][16]. However, although wound infection up to 2.8% has been reported by a few studies in the [14], this complication was not experienced by any of our patients nor in several other reported studies [5,6].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a small underlying seroma after open repair may have been concealed by an edematous and swollen groin wound, thereby giving a low incidence of seroma after Lichtenstein hernioplasty. Our previous study [10] demonstrated that seroma had no impact on the patientÕs recovery, and that virtually all seromas underwent spontaneous resolution. Lichtenstein hernioplasty had a higher incidence of wound morbidity than TEP.…”
Section: Discussionmentioning
confidence: 98%
“…Lau et all found that significant clinical factors associated with seroma formation included old age, large hernia defects, an extension of the hernia into the scrotum, and the presence of a residual distal indirect sac. 17 One case TEP was converted to TAPP procedure due to multiple rents in the peritoneum. Even after insertion of vareese needle for decompression at palmer's point adequate preperitoneal space could not be attained for repair.…”
Section: Discussionmentioning
confidence: 99%